Fight for us Les in soumis ; Orapronobis - Brocka, Lino.; Lacaba, Jose F. 1945-.; Salvador, Philip; Bonnevie, Dina.; Alajar, Gina.; Roco, Bembol; Giancarlo Parretti Production ([S.l.] Giancarlo Parretti Production, 1989)
Jimmy Cordero (Salvador), an ex-priest-turned-underground revolutionary and politcal detainee during Marcos regime, went to a fact-finding mission to Dolores to investigate a right-wing vigilante cult called, "Orapronobis" under the leadership of Kumander Kontra (Roco). He joined his brother-in-law (Roland) despite her wife's, Trixie (Bonnevie), protest. In their way, he met his ex-girlfriend, Esper and their son. With the millitary support, the Orapronobis kept on with their terrorist act. Jimmy's group forced to evacuate the townspeople away from the group and went to Manila. Jimmy's old friends invited him to rejoin the underground movement. During an ambush, Jimmy survived and Roland died. Esper and son were abducted by the Orapronobis who accuse Esper of helping the rebels. She was beaten and raped by Kumander Kontra. She fought back and shot Kontra. Kontra went on a shooting rampage, killing Esper, her son and the captured barrio men. Later, the millitary penetrated the area, told the media that the casualties were rebels and brought them to the town center where Jimmy weeps over the bodies of Esper and his son. After the incident, Jimmy dicided to go back to underground movement.
Subtitle: English
Philip Salvador, Dina Bonnevie, Gina Alajar, Bembol Roco.
Keywords: Guerillas -- Philippines -- Drama; Military -- Philippines -- Drama; Motion pictures -- Philippines